A prospective phase II study of biweekly S-1, leucovorin, and gemcitabine in elderly patients with locally advanced or metastatic pancreatic adenocarcinoma – The Taiwan Cooperative Oncology Group T1217 study. (September 2022) - Bai, Li-Yuan; Li, Chung-Pin; Shan, Yan-Shen; Chuang, Shih-Chang; Chen, Jen-Shi; Chiang, Nai-Jung; Chen, Yen-Yang; Tsou, Hsiao-Hui; Chuang, Mei-Hsing; Chiu, Chang-Fang; Liu, Tsang-Wu; Chen, Li-Tzong
Abstract: Background: Elderly patients with advanced pancreatic adenocarcinoma (APC) are conceived to be frailer and susceptible to treatment toxicity that has led to disparity in lower likelihood of receiving chemotherapy and survival. Optimal chemotherapy is an unmet medical need for elderly patients with APC. Patients and methods: Patients with chemo-naive APC, age ≥70 years, and Eastern Cooperative Oncology Group (ECOG) performance score ≤2 were eligible. The treatment was consisted of biweekly gemcitabine 800 mg/m 2, 10 mg/m 2 /min infusion on day 1 plus oral S-1 and leucovorin (40–60 and 30 mg, respectively) twice daily on days 1–7, the GSL regimen. The primary end-point was progression-free survival with an interested P 1 of 5.0 months. Results: Of the 49 enrolled patients, the median age was 76 years, ECOG performance score ≥1 in 59.2%, metastatic diseases in 65.3%, Vulnerable Elders Survey-13 score ≥3 in 71.4%, and Geriatric 8 score ≤14 in 93.9%. After a median 11 cycles of treatment, the overall response rate and disease control rate were 26.5% and 75.5%, respectively. The median progression-free and overall survivals were 6.6 months (95% confidence interval [CI], 5.4–9.2) and 12.5 months (95% CI, 8.9–14.7), respectively. The most common grade 3–4 treatment-related toxicities were anaemia (20.4%), neutropenia (18.4%), and mucositis (12.2%). Patients had improved emotional function and global health status scores during the GSL treatment. Conclusion: The study met its primary end-point, which supports further investigation on the merit of GSL in Asian elderly APC patients. Highlights: A phase II study of GSL regimen in elderly advanced pancreatic cancer patients. GSL showed activity, tolerability, and safety in this frail group of patients. Improved emotional function and global health status scores during treatment. Further investigation of GSL in Asian elderly APC patients is warranted.